Alterations in key metabolic sensors involved in bovine cystic ovarian disease - Gareis, Natalia Carolina (2018)
High-producing dairy cows frequently suffer metabolic alterations that cause different diseases, which could decrease the reproductive efficiency of the herd. Among these reproductive disorders, cystic ovarian disease (COD) has been related to alterations in metabolites and hormonal factors such as insulin, adiponectin and leptin. The aim of this study was to determine the protein expression of adiponectin and some of its downstream targets in ovarian follicles of control cows and cows with clinical diagnosis of COD. We also analyzed some key metabolic sensors in plasma and follicular fluid from both groups. In follicular cysts, we detected higher protein expression of adiponectin receptor 2 (AdipoR2), 5′ adenosine monophosphate-activated protein kinase (AMPK), carnitine palmitoyl transferase 1 (CPT1) and acyl-coenzyme A oxidase 1 (ACOX1) relative to control antral follicles (p < 0.05). This was related to higher plasma adiponectin concentration in cows with COD than in control cows (p < 0.05). On the other hand, insulin concentrations showed an opposite pattern (p < 0.05). Furthermore, we found alterations in local and systemic concentrations of several metabolites. In this regard, in follicular fluid of cystic cows, the concentrations of non-esterified fatty acids and beta-hydroxybutyrate were higher (p < 0.05), whereas the concentrations of glucose and triacylglycerol were lower than in follicular fluid from control cows (p < 0.05). Besides, in both follicular fluid and plasma of cows with COD, the concentration of cholesterol was higher than in control animals (p < 0.05). These results evidence a local altered scenario of some metabolic sensors in cystic follicles, which could generate an adverse microenvironment for the resumption of ovarian activity, possibly causing the persistence of follicles and the recurrence of COD.